INTEGRATED MARKETING COMMUNICATION NARUNA KERAMIK DALAM MEMBANGUN BRAND AWARENESS PADA MASA PANDEMI - Yvonne Eka Soetristiyono; Zon Vanel (Jurnal Pustaka Komunikasi, 2022)
The challenges faced in the business are getting heavier. Besides the competition, the pandemic caused a heavy blow for Micro Small Medium-Sized Enterprises, resulting in a decrease in business. But, the difference occurs in Naruna Keramik which has grown fast during the pandemic. Therefore this research aims to know and describe the integrated communication strategy of Naruna Keramik to build brand awareness during the pandemic situation. This research is analyzed using five marketing mixes: advertising, sales promotion, personal selling, direct marketing, and public relations. The research uses qualitative methods and descriptive research types. The data in this research are collected using mixed methods including interviews, documentation, observation, and survey. The result is that Naruna Keramik has all of the marketing mixes including advertising, sales promotion, personal selling, direct marketing, and public relations. The use of online media has proven to be effective in optimizing the integrated communication strategy, proven from the most effective marketing mixes in building brand awareness are online advertising and public relations in the social media aspect. The brand awareness of Naruna Keramik is on the brand recall level, where people can memorize and mention the Naruna brand after the top of mind brand.